Copper-based catalyst, preparation method and application thereof, and method for preparing alcohol by hydrogenation of n-butyraldehyde
The copper-based catalyst is prepared by combining ammonia evaporation and hydrothermal method, which solves the problems of low activity, low selectivity and poor stability of existing catalysts, and achieves high activity and high selectivity under mild conditions and excellent hydrogenation reaction Stability and high alcohol selectivity.
Patent Information
- Application Number
- CN202310755891.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
AI Technical Summary
The existing copper-based catalysts have low activity, low selectivity and poor stability in n-butyraldehyde hydrogenation reaction, resulting in harsh reaction conditions and frequent side reactions, which affects the product quality of alcohol.
The copper-based catalyst is prepared by ammonia evaporation and hydrothermal method. Through ammonia evaporation and hydrothermal treatment, a catalyst with uniform dispersion of active components is formed. The reduction peak temperature of CuO is between 150-200°C and is adjusted under the action of the support. The electronic state of the metal enhances the activity and stability of the catalyst.
It improves the activity, selectivity and stability of the catalyst, reduces the occurrence of side reactions, significantly improves the selectivity and mass transfer properties of n-butanol, and is suitable for mild conditions of aldehyde hydrogenation to produce alcohol.
Smart Images

Figure CN119186569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic hydrogenation, and in particular to a copper-based catalyst and a preparation method thereof and an application method thereof and a method for preparing alcohol by hydrogenating n-butyraldehyde. Background Art
[0002] Butanol is an important organic chemical raw material, mainly used to produce esters such as butyl acrylate, butyl acetate, dibutyl phthalate, etc., accounting for about 60% of the total consumption of butanol. In addition, as a fine chemical, butanol is also used in the synthesis of coatings, antioxidants, food additives and chemical extractants, and its application range is constantly expanding. The industrial production technology of butanol mainly consists of the medium-pressure water-soluble rhodium method of Ruhr in Germany, the modified cobalt method of Shell in the United States, the rhodium method of Mitsubishi Chemical, and the modified rhodium method of UCC in the United States. Among them, the low-pressure modified rhodium carbonyl synthesis technology jointly developed by Union Carbide and David is in a leading position in the world carbonyl synthesis industry. This technology uses propylene and synthesis gas as raw materials, and generates butyraldehyde through a low-pressure carbonyl synthesis reaction, and then butyraldehyde is hydrogenated under the action of a catalyst to generate butanol. In industrial production, the hydrogenation process of butyraldehyde is generally divided into a gas phase method and a liquid phase method. Among them, the gas phase method is widely used due to its simple process equipment and low reaction pressure. Most of the butanol production devices introduced in China today use a gas phase hydrogenation process. The catalyst generally used in the gas-phase aldehyde hydrogenation step is a copper-based oxide catalyst, the main components of which are copper, zinc, and aluminum. Generally speaking, the performance of the n-butyraldehyde hydrogenation catalyst is crucial to the efficiency of catalytic aldehyde hydrogenation and the quality index of the hydrogenation product n-butanol. Therefore, the pursuit of copper-based catalysts with high hydrogenation activity, high selectivity, and stability has always been an important goal of the development and research of butyraldehyde gas-phase hydrogenation catalysts.
[0003] CN1883795A discloses a copper-zinc-aluminum gas-phase aldehyde hydrogenation catalyst prepared by a step-by-step continuous precipitation method. In this process, zinc nitrate and aluminum nitrate are neutralized and precipitated by a continuous feeding method, and copper nitrate and zinc nitrate are directly added to precipitate again, so that the catalyst has high metal dispersion, large specific surface area and pore volume.
[0004] CN114054033A discloses a gas-phase aldehyde hydrogenation catalyst, which is prepared by an acid-base two-step precipitation method. First, the metal component is complexed with citric acid, and then the metal is precipitated with carbonate, thereby increasing the specific surface pore volume of the catalyst, improving the internal diffusion performance of the reaction material, and improving the dispersion of the active metal and increasing the number of active centers.
[0005] CN1144715A discloses a copper-zinc-aluminum gas-phase aldehyde hydrogenation catalyst, using sodium metaaluminate as an aluminum source, wherein metaaluminate ions can completely react with zinc ions to form a zinc-aluminum spinel structure, reducing the aluminum oxide present alone in the catalyst, suppressing side reactions, and copper oxide and zinc-aluminum spinel interact and strengthen, improving the dispersion of copper oxide, and improving the activity and stability of the catalyst. These inventions above show to a large extent that the dispersed state of the catalyst active component copper oxide and the nanoparticle thermal stability, the well-developed pore structure of the catalyst, etc. play a very important role in improving the hydrogenation performance of the catalyst. But at the same time, aluminum-containing catalysts often inevitably have certain surface acidity, so some dehydration side reactions occur on the catalyst surface, promote the generation of by-product butyl butyrate, butyl ether, etc., and reduce the selectivity of the target product n-butyl alcohol. In addition, suitable pore structure is conducive to mass transfer and heat transfer, reduces the number of hot spots in the catalyst, and is also conducive to the promotion of product selectivity.
[0006] Therefore, optimizing the composition and pore structure of the catalyst while ensuring the high dispersibility and stability of the active components is of great significance for the preparation of highly active and highly selective n-butyraldehyde hydrogenation catalysts. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of harsh reaction conditions, low catalyst activity, low selectivity and poor catalyst stability in the prior art catalyst for aldehyde hydrogenation to alcohol, and to provide a copper-based catalyst and a preparation method thereof and a method for using the same in the hydrogenation of n-butyraldehyde to prepare alcohol. The catalyst has high catalytic activity and selectivity under mild conditions and excellent stability.
[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a copper-based catalyst, which comprises an active component copper oxide, an optional auxiliary metal oxide and a carrier, wherein the reduction peak temperature of CuO in the copper-based catalyst in H2-TPR is between 150-200°C.
[0009] The second aspect of the present invention provides a method for preparing the copper-based catalyst of the present invention, the preparation method comprising:
[0010] a. evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex and an optional auxiliary metal ammine complex to obtain a second mixed solution;
[0011] b. The second mixed liquid is subjected to hydrothermal treatment, filtration, washing, drying, roasting and molding.
[0012] The third aspect of the present invention provides an application of the copper-based catalyst of the present invention in the hydrogenation of aldehydes to alcohols.
[0013] A fourth aspect of the present invention provides a method for preparing alcohol by hydrogenating n-butyraldehyde, the method comprising: contacting a n-butyraldehyde raw material with hydrogen in the presence of a catalyst;
[0014] The catalyst is the copper-based catalyst described in the first aspect after reduction activation.
[0015] Compared with the prior art, the present invention has the advantages of:
[0016] The active components of the catalyst provided by the present invention are evenly dispersed, which can improve the utilization rate of metals, enhance the mass and heat transfer performance in the catalyst, reduce the existence of reaction hot spots and the occurrence of overheating side reactions, and the catalyst has high activity, high selectivity and good stability.
[0017] In the preparation method of the catalyst provided by the present invention, the ammonia evaporation method is combined with the hydrothermal method to prepare the catalyst of the structure of the present invention, and the interaction between the catalyst metal component and the carrier is strengthened, the electronic state of the active metal is adjusted, the effective adsorption of the reactant is promoted, and the activity and stability of the catalyst are improved. At the same time, the defect that the conventional ammonia evaporation method cannot effectively load the auxiliary metal is overcome.
[0018] The catalyst provided by the invention is suitable for preparing alcohols by hydrogenating aldehydes, and is particularly suitable for preparing butanol by hydrogenating n-butyraldehyde, and has high butanol selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the nitrogen adsorption-desorption curve of the catalyst obtained in Example 1;
[0020] Figure 2 is the pore size distribution curve of the catalyst obtained in Example 1;
[0021] Figure 3 is the XRD spectrum of the catalyst obtained in Example 1;
[0022] Figure 4 is the H2-TPR spectrum of the catalyst obtained in Example 1;
[0023] Figure 5 This is the evaluation result of the stability of the butyraldehyde gas phase hydrogenation performance of the catalyst obtained in Example 1. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The invention provides a copper-based catalyst, which comprises an active component of copper oxide, an optional auxiliary metal oxide and a carrier. The reduction peak temperature of CuO in the copper-based catalyst in H2-TPR is between 150-200°C.
[0026] The active components of the catalyst provided by the present invention are evenly dispersed, which can improve the utilization rate of metals, enhance the mass and heat transfer performance in the catalyst, reduce the existence of reaction hot spots and the occurrence of overheating side reactions, and the catalyst has high activity, high selectivity and good stability.
[0027] According to a preferred embodiment of the present invention, the reduction peak temperature of CuO in the copper-based catalyst in H2-TPR is between 160-190°C.
[0028] In the present invention, the auxiliary metal oxide has a wide range of options. According to a particularly preferred embodiment of the present invention, the auxiliary metal oxide comprises at least one of nickel oxide, cobalt oxide and zinc oxide.
[0029] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of each component in the auxiliary metal oxide. According to a particularly preferred embodiment of the present invention, the mass ratio of nickel oxide, cobalt oxide and zinc oxide in the auxiliary metal oxide is 0.01-0.5: 0.01-2: 1. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0030] According to a particularly preferred embodiment of the present invention, the specific surface area of the copper-based catalyst is 150-400m 2 g -1 By adopting the above-mentioned preferred embodiments, the activity, selectivity and stability of the catalyst can be further improved.
[0031] According to a particularly preferred embodiment of the present invention, the specific surface area of the copper-based catalyst is 180-350 m 2 g -1 .
[0032] According to a particularly preferred embodiment of the present invention, the pore volume of the copper-based catalyst is 0.4-0.8 cm 2 g -1 By adopting the above-mentioned preferred embodiments, the activity, selectivity and stability of the catalyst can be further improved.
[0033] According to a particularly preferred embodiment of the present invention, the pore volume of the copper-based catalyst is 0.5-0.7 cm 2 g -1 .
[0034] According to a particularly preferred embodiment of the present invention, the most probable pore size of the copper-based catalyst is 6.0-20.0 nm. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0035] According to a particularly preferred embodiment of the present invention, the most probable pore size of the copper-based catalyst is 8-16 nm.
[0036] According to a particularly preferred embodiment of the present invention, the average crystal size of the additive metal oxide in the copper-based catalyst is between 2 and 8 nm. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0037] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of each component of the catalyst. According to a particularly preferred embodiment of the present invention, the copper-based catalyst comprises, by mass: a copper oxide content of 10-45%; an auxiliary metal oxide content of 0-25%; and a carrier content of 30-90%.
[0038] According to a particularly preferred embodiment of the present invention, the copper-based catalyst comprises, by mass, 15%-40% copper oxide, 5%-20% auxiliary metal oxide, and 40%-80% carrier. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0039] In the present invention, the carrier has a wide range of options, and according to a particularly preferred embodiment of the present invention, the carrier is silicon dioxide. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0040] According to a particularly preferred embodiment of the present invention, the carrier is selected from silicon dioxide modified by at least one modifier selected from the group consisting of molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide.
[0041] According to a particularly preferred embodiment of the present invention, the content of the modifier in the silicon dioxide modified with the modifier is 3-25 wt %.
[0042] The present invention provides a method for preparing the copper-based catalyst of the present invention, the preparation method comprising:
[0043] a. evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex and an optional auxiliary metal ammine complex to obtain a second mixed solution;
[0044] b. The second mixed liquid is subjected to hydrothermal treatment, filtration, washing, drying, roasting and molding.
[0045] In the preparation method of the catalyst provided by the present invention, the ammonia distillation method is combined with the hydrothermal method to prepare the catalyst of the structure of the present invention, and the interaction between the catalyst metal component and the carrier is strengthened, the electronic state of the active metal is adjusted, the effective adsorption of the reactants is promoted, and the activity and stability of the catalyst are improved.
[0046] According to a particularly preferred embodiment of the present invention, the preparation method of the first mixed solution comprises mixing and dissolving a carrier source, a copper source, an optional auxiliary metal source and an ammonia source. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0047] According to a particularly preferred embodiment of the present invention, the copper source and the optional auxiliary metal source are first dissolved, and then the ammonia source is added, and then the carrier source is added, and mixed to obtain a first mixed solution. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0048] According to a particularly preferred embodiment of the present invention, the ammonia source is selected from ammonia water and / or ammonia gas.
[0049] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular requirement for the concentration of the aqueous ammonia. According to a particularly preferred embodiment of the present invention, the concentration of the aqueous ammonia is 10-28wt%. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.
[0050] In the present invention, the dissolving solvent has a wide selection range, and commonly used dissolving solvents can be used in the present invention. According to a particularly preferred embodiment of the present invention, the dissolving solvent is selected from at least one of water, methanol, and ethanol.
[0051] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular requirement for the difference between the pH of the first mixed solution and the pH of the second mixed solution. According to a preferred embodiment of the present invention, the difference between the pH of the first mixed solution and the pH of the second mixed solution is 4 to 6. By adopting the above preferred embodiment, the activity, selectivity and stability of the prepared catalyst can be further improved.
[0052] According to a particularly preferred embodiment of the present invention, the pH of the first mixed solution is 11 to 12. By adopting the above preferred embodiment, the activity, selectivity and stability of the prepared catalyst can be further improved.
[0053] According to a particularly preferred embodiment of the present invention, the pH of the second mixed solution is 6 to 7. By adopting the above preferred embodiment, the activity, selectivity and stability of the prepared catalyst can be further improved.
[0054] In the present invention, the evaporation conditions can be conventionally selected in the art. According to a particularly preferred embodiment of the present invention, the evaporation conditions include: a temperature of 70-90° C., preferably 75-85° C. The time is determined according to the temperature, and the main purpose is to evaporate and remove ammonia in the first mixed solution, and no special requirements are made on the time.
[0055] In the present invention, the conditions for the hydrothermal treatment can be selected according to conventional techniques in the art. According to a particularly preferred embodiment of the present invention, the conditions for the hydrothermal treatment include: a temperature of 130-150°C, and a time that can be determined according to the temperature, for example, 24-28 hours.
[0056] According to a particularly preferred embodiment of the present invention, the hydrothermal treatment conditions include: a temperature of 140-150° C., and a time that can be determined according to the temperature, for example, 36-48 hours. By adopting the above preferred scheme, the activity, selectivity and stability of the prepared catalyst can be further improved.
[0057] According to a particularly preferred embodiment of the present invention, the drying conditions include: a temperature of 80-120° C., preferably 80-100° C., and a time that can be determined according to the temperature, for example, 6-12 hours.
[0058] According to a particularly preferred embodiment of the present invention, the drying conditions include: a temperature of 80-100° C., and a time that can be determined according to the temperature, for example, 8-12 hours.
[0059] In the present invention, the calcination conditions can be selected according to conventional techniques in the art. According to a particularly preferred embodiment of the present invention, the calcination conditions include: an oxygen-containing atmosphere, a temperature of 300-400° C., and a time of 2-8 h.
[0060] In the present invention, the calcination conditions can be selected according to conventional techniques in the art. According to a particularly preferred embodiment of the present invention, the calcination conditions include: a temperature of 300-380° C. and a time of 4-8 h in an oxygen-containing atmosphere. By adopting the above preferred scheme, the activity, selectivity and stability of the prepared catalyst can be further improved.
[0061] According to a particularly preferred embodiment of the present invention, the oxygen-containing atmosphere is an air atmosphere.
[0062] In the present invention, the copper source has a wide range of optional types, and all commonly used types can be used in the present invention. According to a particularly preferred embodiment of the present invention, the copper source is a copper compound, preferably a copper salt.
[0063] According to a particularly preferred embodiment of the present invention, the copper source is selected from at least one of copper nitrate, copper chloride, copper acetate and copper sulfate.
[0064] In the present invention, the types of the auxiliary metal source can be selected from a wide range, and commonly used types can be used in the present invention. According to a particularly preferred embodiment of the present invention, the auxiliary metal source is at least one of a nickel compound, a cobalt compound and a zinc compound, preferably at least one of a nickel salt, a cobalt salt and a zinc salt.
[0065] According to a particularly preferred embodiment of the present invention, the auxiliary metal source is at least one of nitrates, hydrochlorides, acetates and sulfates of nickel, cobalt and zinc, respectively.
[0066] In the present invention, the types of the carrier source can be selected from a wide range. According to a particularly preferred embodiment of the present invention, the carrier source is an organic silicon source or an inorganic silicon source. Preferably, the silicon source is at least one of silicon dioxide, silica sol, and TEOS.
[0067] According to a particularly preferred embodiment of the present invention, the silicon source is silicon dioxide modified by at least one modifier selected from the group consisting of molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide.
[0068] According to a particularly preferred embodiment of the present invention, the mixing is carried out by stirring, preferably for at least 2 hours.
[0069] According to a particularly preferred embodiment of the present invention, during the evaporation process, solvent is appropriately added to prevent the solution from drying up.
[0070] The present invention provides an application of the copper-based catalyst of the present invention in preparing alcohol by hydrogenating aldehyde.
[0071] According to a particularly preferred embodiment of the present invention, the use of the copper-based catalyst in the hydrogenation of aldehydes to produce alcohols is preferably the use of the copper-based catalyst in the hydrogenation of C2-C5 aldehydes to produce alcohols.
[0072] According to a particularly preferred embodiment of the present invention, the copper-based catalyst is used in the hydrogenation of n-butyraldehyde to alcohol.
[0073] The invention provides a method for preparing alcohol by hydrogenating n-butyraldehyde, which comprises: contacting and reacting n-butyraldehyde raw material with hydrogen in the presence of a catalyst; the catalyst is the copper-based catalyst of the invention after reduction activation.
[0074] The catalyst provided by the invention is particularly suitable for preparing butanol by hydrogenating n-butyraldehyde. The catalyst inhibits the occurrence of a dehydration side reaction, reduces the generation of by-products, and significantly improves the selectivity of the target product butanol.
[0075] According to a particularly preferred embodiment of the present invention, the molding method includes tableting and / or extrusion, and optionally crushing and screening are performed after molding to obtain a granular catalyst with a particle size of 10-20 mesh.
[0076] In the present invention, the conditions of the contact reaction can be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions of the contact reaction include: a reaction temperature of 100-150°C, preferably 110-130°C; a reaction pressure of 0.3-0.8MPa, preferably 0.4-0.6MPa; a liquid space velocity of n-butyraldehyde of 0.2-1.0h -1 , preferably 0.3-0.6; the molar ratio of hydrogen to formaldehyde is 10-30:1, preferably 15-20:1.
[0077] According to a particularly preferred embodiment of the present invention, the reduction activation conditions include: reduction temperature of 180-280° C., preferably 200-260° C., and time of 8-12 h, preferably 8-10 h.
[0078] According to a particularly preferred embodiment of the present invention, physically adsorbed water is removed before the reduction activation, and the conditions include: heating to 120-150° C. and maintaining for 4-8 hours in an inert atmosphere, preferably a nitrogen atmosphere.
[0079] In order to make the present invention easier to understand, the present invention will be described in detail below in conjunction with examples. These examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials involved in the examples are all commercially available unless otherwise specified.
[0080] In the present invention, H2-TPR is carried out on a BELCATⅡ, MicrotracBEL instrument, with a reducing gas of 5 vol% H2 / Ar. Before the sample is tested, it is first purged in Ar at 200°C for 2h, and then the sample TPR curve is collected from room temperature to 700°C, with a heating rate of 5°C / min.
[0081] In the present invention, the amount of acid on the catalyst surface is determined by the NH3-TPD method: 10 vol% NH3 / Ar is performed on a BELCATⅡ, MicrotracBEL instrument. Before the sample is tested, it is first purged in Ar at 200°C for 2 hours, and after cooling to 100°C, the sample adsorbs 10 vol% NH3 / Ar for 30 minutes, and then switches to Ar purging for 1 hour. The TPD curve is collected from 100°C to 600°C, with a heating rate of 5°C / min
[0082] In the present invention, XRD spectrum: Philip X'pert Pro diffractometer is used to collect XRD spectrum of the catalyst, the X-ray radiation source is Cu target Kα ray (λ=0.15408nm) filtered by Ni filter, the collection step is 0.06° / s, the X-ray tube operating voltage is 40kV, and the current is 40mA. The average grain size of CuO is calculated according to the XRD data using Scherrer formula.
[0083] In the present invention, the pore structure properties of the sample were tested using a Micromeritics ASAP-3020 physical adsorption instrument. The sample was degassed at 300°C for 3 hours before the test, and the test was performed at liquid nitrogen temperature (-196°C). The specific surface area of the sample was calculated by the Brunauer-Emmett-Teller (BET) multilayer physical adsorption model, and the pore size distribution was obtained by the Barrett-Joyner-Halenda method.
[0084] Example 1
[0085] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-1. After testing, the specific surface area of the catalyst HC-1 was 332m 2 g -1 , pore volume is 0.68cm 2 g -1 , the most probable pore size is 10.3 nm, the average grain size of the additive metal oxide is 3.2 nm, and the reduction peak temperature of CuO in H2-TPR is 182 °C.
[0086] Figure 1 and Figure 2 The nitrogen adsorption-desorption curve and pore size distribution curve of the catalyst prepared in this example indicate that the catalyst has a rich mesoporous structure.
[0087] Figure 3 The XRD spectrum of the catalyst prepared in this example shows the diffraction peaks of the active metal CuO (in the XRD spectrum, there are characteristic peaks at 2θ=35.4±1° and 38.2±1°).
[0088] Figure 4 The H2-TPR spectrum of the catalyst prepared in this example shows a characteristic peak attributed to the reduction of copper oxide.
[0089] Example 2
[0090] Weigh 47.157g of copper nitrate trihydrate and 23.274g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 50g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-2. After testing, the specific surface area of the catalyst HC-2 was 198m 2 g -1 , pore volume is 0.54cm 2 g -1 , the most probable pore size is 8.6 nm, the average grain size of the additive metal oxide is 6.4 nm, and the reduction peak temperature of CuO in H2-TPR is 177 °C.
[0091] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-2 are similar to those of HC-1.
[0092] Example 3
[0093] Weigh 47.157g of copper nitrate trihydrate, 7.749g of zinc nitrate hexahydrate, 7.353g of nickel nitrate hexahydrate and 8.153g of cobalt nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salts, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 hours, ground into powder, placed in a muffle furnace and calcined at 350° C. in air for 4 hours. The obtained sample was tableted, crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-3.
[0094] The specific surface area of catalyst HC-3 was found to be 245 m 2 g -1 , pore volume is 0.63cm 2 g -1 , the most probable pore size is 12.3 nm, the average grain size of the additive metal oxide is 3.8 nm, and the reduction peak temperature of CuO in H2-TPR is 161 °C.
[0095] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-3 are similar to those of HC-1.
[0096] Example 4
[0097] Weigh 47.157g of copper nitrate trihydrate and 22.060g of cobalt nitrate hexahydrate into a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 50g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-4. After testing, the specific surface area of the catalyst HC-4 was 203m 2 g -1 , pore volume is 0.55cm 2 g -1 , the most probable pore size is 9.6 nm, the average grain size of the additive metal oxide is 5.6 nm, and the reduction peak temperature of CuO in H2-TPR is 188 °C.
[0098] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-4 are similar to those of HC-1.
[0099] Example 5
[0100] Weigh 47.157g of copper nitrate trihydrate and 24.460g of nickel nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 50g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-5. After testing, the specific surface area of the catalyst HC-5 was 188m 2 g -1 , pore volume is 0.51cm 2 g -1 , the most probable pore size is 9.4 nm, the average grain size of the additive metal oxide is 5.2 nm, and the reduction peak temperature of CuO in H2-TPR is 179 °C.
[0101] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-5 are similar to those of HC-1.
[0102] Example 6
[0103] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 20g of silicon dioxide powder and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-6. After testing, the specific surface area of the catalyst HC-6 was 376m 2 g -1 , pore volume is 0.74cm 2 g -1 , the most probable pore size is 12.4 nm, the average grain size of the additive metal oxide is 5.8 nm, and the reduction peak temperature of CuO in H2-TPR is 181 °C.
[0104] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-6 are similar to those of HC-1.
[0105] Example 7
[0106] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 8 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-7. After testing, the specific surface area of the catalyst HC-7 was 254m 2 g -1 , pore volume is 0.45cm 2 g -1 , the most probable pore size is 8.6 nm, the average grain size of the additive metal oxide is 6.2 nm, and the reduction peak temperature of CuO in H2-TPR is 186 °C.
[0107] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-7 are similar to those of HC-1.
[0108] Example 8
[0109] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 14, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 8 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-8. After testing, the specific surface area of the catalyst HC-8 was 224m 2 g -1 , pore volume is 0.39cm 2 g -1 , the most probable pore size is 8.5 nm, the average grain size of the additive metal oxide is 6.3 nm, and the reduction peak temperature of CuO in H2-TPR is 190 °C.
[0110] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-8 are similar to those of HC-1.
[0111] Example 9
[0112] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 180℃ oven for hydrothermal treatment for 8 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 150℃ for 4 hours, it was ground into powder and placed in a muffle furnace and calcined in air at 350℃ for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-9. After testing, the specific surface area of the catalyst HC-9 was 145m 2 g -1 , pore volume is 0.36cm 2 g -1 , the most probable pore size is 25.4 nm, the average grain size of the additive metal oxide is 8.5 nm, and the reduction peak temperature of CuO in H2-TPR is 200 °C.
[0113] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-9 are similar to those of HC-1.
[0114] Example 10
[0115] Weigh 30.292g of ferric nitrate nonahydrate and 13.246g of citric acid into a beaker, add 100g of deionized water and stir to dissolve, then add 20g of mesoporous silica SBA-15 into the solution, and continue stirring the mixture for 2h. Transfer the mixture to an 80℃ oil bath to heat and evaporate the water, place the solid in a 100℃ oven to dry for 12h, and then place it in a tubular furnace and calcine at 450℃ for 4h in a nitrogen atmosphere to obtain a modified silica carrier.
[0116] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 20g of modified silica carrier and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250ml high-pressure hydrothermal autoclave, and placed in a 150℃ oven for hydrothermal heating for 24 hours. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water 3 times. After the filter cake was dried in an oven at 100℃ for 8 hours, it was ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4 hours. The obtained sample was tableted, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as HC-10. After testing, the specific surface area of the catalyst HC-10 was 316m 2 g -1 , pore volume is 0.59cm 2 g -1 , the most probable pore size is 8.9 nm, the average grain size of the additive metal oxide is 3.5 nm, and the reduction peak temperature of CuO in H2-TPR is 166 °C.
[0117] The nitrogen adsorption-desorption curve, pore size distribution curve and XRD spectrum of HC-10 are similar to those of HC-1.
[0118] Comparative Example 1
[0119] Same as Example 3, except that the catalyst was prepared by precipitation method:
[0120] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 250ml beaker, add 100g of deionized water and stir until completely dissolved, then transfer all the solutions to a stirred reactor, set the heating temperature to 60°C, and the stirring rate to 150rpm; then weigh 37.206g of ammonium carbonate in a 250ml beaker, add 100g of deionized water and stir until completely dissolved, then transfer the solution to a measuring cylinder and dilute to 250ml; weigh 86.699g of TEOS in a 250ml beaker, first add 150g of deionized water to dissolve, then transfer the solution to a measuring cylinder, and then add anhydrous ethanol to dilute to 250ml. Use a peristaltic pump to flow the aluminum nitrate solution and the ammonium carbonate solution into the stirred reactor, maintain the temperature and speed in the stirred reactor, where the flow rate of the aluminum nitrate solution is 10ml / min, and the flow rate of the ammonium carbonate solution is 10ml / min. After the addition was completed, the slurry in the reactor was aged at 60°C for 6 hours, then filtered, the filter cake was washed with deionized water 3 times, transferred to a 100°C oven for drying for 12 hours, and then placed in a muffle furnace for calcination at 350°C for 4 hours. The obtained solid was ground into powder, pressed into tablets using an electric tablet press, and crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, recorded as DB-1. After testing, the specific surface area of catalyst DB-1 was 123m 2 g -1 , pore volume is 0.26cm 2 g -1 , the most probable pore size is 24.6 nm, the average grain size of the additive metal oxide is 11.5 nm, and the reduction peak temperature of CuO in H2-TPR is 244 °C.
[0121] The XRD spectrum of DB-1 has characteristic peaks at 2θ=46.1° and 68.2°.
[0122] Comparative Example 2
[0123] Same as Example 3, except that no hydrothermal treatment is performed:
[0124] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 62.5g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Then heat the first mixed solution to 80℃, evaporate the ammonia in the solution, add 30g of deionized water 3 times during the period to ensure that the solution is not evaporated, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The mixed solution is filtered, and the filter cake is washed with deionized water 3 times; after the filter cake is dried in an oven at 100℃ for 8h, it is ground into powder and placed in a muffle furnace and calcined at 350℃ in air for 4h. The obtained sample is pressed, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which is recorded as DB-2. The specific surface area of catalyst DB-3 was found to be 196 m 2 g -1 , pore volume is 0.45cm 2 g -1 , the most probable pore size is 10.5 nm, the average grain size of the additive metal oxide is 5.6 nm, and the reduction peak temperature of CuO in H2-TPR is 205 °C.
[0125] The XRD spectrum of DB-3 has characteristic peaks at 2θ=35.1° and 38.2°.
[0126] Comparative Example 3
[0127] Weigh 47.157g of copper nitrate trihydrate and 11.637g of zinc nitrate hexahydrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 62.5g of 40% silica sol and add it to the above solution, continue stirring and mixing for 4h to obtain a mixed solution. Transfer the mixed solution in the beaker to a 250ml high-pressure hydrothermal autoclave, put it in a 150℃ oven for hydrothermal treatment for 24h, finally take out the hydrothermal autoclave and cool it to room temperature, filter the mixed solution in the hydrothermal autoclave, and wash the filter cake with deionized water 3 times; after drying the filter cake in an oven at 100℃ for 8h, grind it into powder and put it in a muffle furnace and roast it at 350℃ in air for 4h, and the obtained sample is pressed, crushed, and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which is recorded as HC-3. The specific surface area of catalyst HC-3 was found to be 181 m 2 g -1 , pore volume is 0.36cm 2 g -1, the most probable pore size is 10.3 nm, the average grain size of the additive metal oxide is 6.1 nm, and the reduction peak temperature of CuO in H2-TPR is 223 °C.
[0128] The XRD spectrum of DB-3 has characteristic peaks at 2θ=35.2° and 38.0°.
[0129] Embodiment 11
[0130] 10 ml of the catalyst prepared in the above examples and comparative examples was loaded into a solid bed reactor. First, the temperature was raised to 120°C in a nitrogen atmosphere for 4 hours to remove physically adsorbed water on the catalyst surface, and then the temperature was lowered to room temperature. The atmosphere was then switched to hydrogen, the temperature was raised to 250°C and maintained for 8 hours to obtain a reduction-activated catalyst, which was then directly used for the performance evaluation of the n-butyraldehyde gas phase hydrogenation reaction. The n-butyraldehyde raw material was gasified in a gasifier before entering the reactor. The hydrogenation process conditions were as follows: reaction temperature 120°C, reaction pressure 0.4 MPa, n-butyraldehyde liquid space velocity 0.5 h -1 , the hydrogen-formaldehyde molar ratio is 20:1, and the reaction product is quantified by gas chromatography, and the chromatographic detector is FID. The results of n-butyraldehyde hydrogenation of the catalysts of various examples are shown in Table 1.
[0131] Figure 5 The catalytic stability of the catalyst prepared in Example 1 was evaluated, and the results showed that it had good and stable catalytic activity within 160 hours, which was significantly improved compared with 50 hours for the catalysts prepared in Comparative Examples 1-3.
[0132] Example 12
[0133] The catalyst prepared in Example 1 was used in the same manner as in Example 11, except that isobutyraldehyde was used as the reaction raw material. The conversion rate and selectivity were measured to be 99.0% and 99.2%, respectively.
[0134] Table 1
[0135] catalyst Silicon source Butyraldehyde conversion rate / % Butanol selectivity / % HC-1 Silica Sol 99.1 99.2 HC-2 Silica Sol 99.2 99.1 HC-3 Silica Sol 99.8 99.8 HC-4 Silica Sol 99.1 99.1 HC-5 Silica Sol 99.0 99.3 HC-6 <![CDATA[SiO2 powder]]> 99.2 99.3 HC-7 Silica Sol 98.6 99.0 HC-8 Silica Sol 99.1 99.1 HC-9 Silica Sol 98.5 99.0 HC-10 Modified silica 99.8 99.9 DB-1 TEOS 83.5 74.2 DB-2 Silica Sol 91.2 90.6 DB-3 Silica Sol 86.9 88.4
[0136] It can be seen from the results in Table 1 that the catalyst prepared by the embodiment of the technical solution of the present invention has significantly better aldehyde conversion rate and alcohol selectivity, and excellent stability.
[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copper-based catalyst, characterized in that The catalyst comprises active component copper oxide, optional auxiliary metal oxide and a carrier. The reduction peak temperature of CuO in the copper-based catalyst in H2-TPR is between 150-200 DEG C.
2. The copper-based catalyst according to claim 1, wherein The reduction peak temperature of CuO in the copper-based catalyst in H2-TPR is between 160-190°C; The auxiliary metal oxide comprises at least one of nickel oxide, cobalt oxide and zinc oxide; Preferably, the auxiliary metal oxide comprises nickel oxide, cobalt oxide and zinc oxide, and preferably the mass ratio of nickel oxide, cobalt oxide and zinc oxide is 0.01-1.5:0.01-2:
1.
3. The copper-based catalyst according to claim 1 or 2, wherein The average crystal size of the auxiliary metal oxide in the copper-based catalyst is between 2 and 8 nm.
4. The copper-based catalyst according to any one of claims 1 to 3, wherein The specific surface area of the copper-based catalyst is 150-400m 2 g -1 , preferably 180-350m 2 g -1 ; and / or The pore volume of the copper-based catalyst is 0.4-0.8 cm 2 g -1 , preferably 0.5-0.7cm 2 g -1 ; and / or The most probable pore size of the copper-based catalyst is 6.0-20.0 nm, preferably 8-16 nm.
5. The copper-based catalyst according to any one of claims 1 to 4, wherein The copper-based catalyst comprises, by mass, 10-45% copper oxide, preferably 15%-40%; 0-25% auxiliary metal oxide, preferably 5%-20%; and 30-90% carrier, preferably 40-80%.
6. The copper-based catalyst according to any one of claims 1 to 5, wherein The carrier is silicon dioxide, more preferably silicon dioxide modified by at least one modifier selected from molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide; more preferably, the content of the modifier in the silicon dioxide modified by the modifier is 3-25wt%.
7. The method for preparing a copper-based catalyst according to any one of claims 1 to 6, characterized in that: The preparation method comprises: a. evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex and an optional auxiliary metal ammine complex to obtain a second mixed solution; b. The second mixed liquid is subjected to hydrothermal treatment, filtration, washing, drying, roasting and molding.
8. The preparation method according to claim 7, wherein: The preparation method of the first mixed solution comprises mixing and dissolving a carrier source, a copper source, an optional auxiliary metal source and an ammonia source; Preferably, the copper source and the optional auxiliary metal source are first dissolved, and then the ammonia source is added, and then the carrier source is added, and mixed to obtain a first mixed solution; More preferably, The ammonia source is selected from aqueous ammonia and / or ammonia gas, and preferably the concentration of aqueous ammonia is 10-28 wt %; and / or The dissolving solvent is selected from at least one of water, methanol and ethanol.
9. The preparation method according to claim 7 or 8, wherein: The difference between the pH of the first mixed solution and the pH of the second mixed solution is 4-6; preferably, The pH of the first mixed solution is 11-12; and / or The pH of the second mixed solution is 6-7.
10. The preparation method according to any one of claims 7 to 9, wherein: The evaporation conditions include: a temperature of 70-90°C, preferably 75-85°C; and / or The conditions of the hydrothermal treatment include: a temperature of 130-150° C., preferably 140-150° C.; and / or a time of 24-28 hours, preferably 36-48 hours; and / or The drying conditions include: a temperature of 80-120°C, preferably 80-100°C; and / or a time of 6-12h, preferably 8-12h; and / or The calcination conditions include: in an oxygen-containing atmosphere, a temperature of 300-400° C., preferably 300-380° C.; and / or a calcination time of 2-8 hours, preferably 4-8 hours.
11. The preparation method according to any one of claims 7 to 10, wherein: The copper source is a copper compound, preferably a copper salt, more preferably at least one selected from copper nitrate, copper chloride, copper acetate and copper sulfate; and / or The auxiliary metal source is at least one of a nickel compound, a cobalt compound and a zinc compound, preferably at least one of a nickel salt, a cobalt salt and a zinc salt, more preferably at least one of a nitrate, a hydrochloride, an acetate and a sulfate of nickel, cobalt and zinc respectively; and / or The carrier source is an organic silicon source and / or an inorganic silicon source, and preferably the silicon source is at least one of silicon dioxide, silica sol, and TEOS.
12. Use of the copper-based catalyst according to any one of claims 1 to 6 in hydrogenation, preferably in the hydrogenation of aldehydes to alcohols, preferably in the hydrogenation of C2-C5 aldehydes to alcohols, more preferably in the hydrogenation of n-butyraldehyde to alcohols.
13. A method for preparing alcohol by hydrogenating n-butyraldehyde, characterized in that: The method comprises: in the presence of a catalyst, contacting a normal butyraldehyde raw material with hydrogen for reaction; The catalyst is a copper-based catalyst according to any one of claims 1 to 6 after reduction activation.
14. The method according to claim 13, wherein: The conditions of the contact reaction include: the reaction temperature is 100-150°C, preferably 110-130°C; and / or the reaction pressure is 0.3-0.8 MPa, preferably 0.4-0.6 MPa; and / or the liquid space velocity of n-butyraldehyde is 0.2-1.0 h -1 , preferably 0.3-0.6h -1 ; and / or a hydrogen-formaldehyde molar ratio of 10-30:1, preferably 15-20:1; and / or The conditions for reduction activation include: a reduction temperature of 180-280° C., preferably 200-260° C.; and / or a reduction time of 8-12 h, preferably 8-10 h.
Citation Information
Cited By
Large-aperture alumina-loaded copper-based catalyst and preparation and application thereof
CN119857488A